2008
DOI: 10.1002/bit.21952
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatibility, interactions, and uptake of polyethyleneimine‐coated boron nitride nanotubes by living cells: Confirmation of their potential for biomedical applications

Abstract: Boron nitride nanotubes (BNNTs) have unique physical properties, which can be exploited in the biomedical field. Hence, the surprising lack of reported studies on their biocompatibility and interactions with living cells, addressed by the present paper which deals the results of such an investigation based on 72 h culture of human neuroblastoma cell line (SH-SY5Y) in the presence of an aqueous suspension of polyethyleneimine (PEI)-coated BNNTs. BNNTs conjugated with fluorescent markers (quantum dots) are emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
172
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(176 citation statements)
references
References 35 publications
4
172
0
Order By: Relevance
“…Research results show that poly ethylene imine modified BNNTs does not produce great influence [9] on neuroblastoma survival, metabolism and cell regeneration. Their subsequent studies showed that the BNNTs modified by poly lysine had good cell compatibility with glioblastoma and fibroblast cells.…”
Section: Introductionmentioning
confidence: 99%
“…Research results show that poly ethylene imine modified BNNTs does not produce great influence [9] on neuroblastoma survival, metabolism and cell regeneration. Their subsequent studies showed that the BNNTs modified by poly lysine had good cell compatibility with glioblastoma and fibroblast cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ciofani et al [7,8] conducted a wide study of the biocompatibility of nanotubes of boron nitride (BNNTs) and their biomedical applications, and the Golberg and Bando group recently reported the transport of a drug that helps decrease cancer using nanosheets of BN with high solubility in water [9]. From the physical-chemical point of view, nanosheets of boron nitride with hexagonal symmetry (hBNNs) are comprised of one mesh of atoms of B and N ordered and alternated in a hexagonal array similar to graphene with sp 2 hybridization; from its gap value of 5.92 eV, hBNN is classified as a semiconductor [10].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Therefore, it is considered promising for biomedical applications, such as drug delivery. [17][18][19][20][21][22][23] Recently, applications of BN nanospheres (BNNS) as carriers for DNA or chemotherapy drugs have only begun to emerge. [24][25][26][27][28] Moreover, BNNS are composed of a substantial number of boron atoms, which can serve as boron carriers…”
Section: Introductionmentioning
confidence: 99%